Thoracoscopic resection of a huge esophageal dedifferentiated liposarcoma: A case report - Ye, Yi-Wang (World J Clin Cases, 2020)
BACKGROUND: Esophageal liposarcoma is a rare malignant tumor and an esophageal dedifferentiated liposarcoma (DDL) is extremely rare. There are no reports on the treatment of DDL by thoracoscopic surgery. CASE SUMMARY: A 38-year-old woman presented with dysphagia and dyspnea. Imaging examination showed a large mass in the posterior mediastinum. The patient also developed respiratory failure and it was unclear whether this was caused by a mass from inside or outside the esophagus. We decided to perform thoracoscopic exploration to relieve the obstruction caused by tracheal compression. The upper segment of the esophagus was split longitudinally, and most of the mass could be removed from the esophageal lumen to the thoracic cavity. The pedicle was excised by linear cutting closers under mirrors. Little residual mass was visualized by gastroscopy. The mucous and muscular layers were closed by interrupted sutures. Pathological examination showed that the mass was a DDL. The patient did not have any dysphagia or dyspnea 2 wk postoperatively and refused any further treatment. Computed tomography and esophagoscopy did not find any recurrence at up to 20 mo postoperatively. CONCLUSION: Thoracoscopy can be used to treat large esophageal masses.